Alkynyl‐Protected Chiral Bimetallic Ag22Cu7 Superatom with Multiple Chirality Origins. Issue 12 (18th January 2023) - Deng, Guocheng; Lee, Kangjae; Deng, Hongwen; Malola, Sami; Bootharaju, Megalamane S.; Häkkinen, Hannu; Zheng, Nanfeng; Hyeon, Taeghwan
Abstract: Understanding the origin of chirality in the nanostructured materials is essential for chiroptical and catalytic applications. Here we report a chiral AgCu superatomic cluster, [Ag22 Cu7 (C≡CR)16 (PPh3 )5 Cl6 ](PPh4 ), Ag22 Cu7, protected by an achiral alkynyl ligand (HC≡CR: 3, 5‐bis(trifluoromethyl)phenylacetylene). Its crystal structure comprises a rare interpenetrating biicosahedral Ag17 Cu2 core, which is stabilized by four different types of motifs: one Cu(C≡CR)2, four −C≡CR, two chlorides and one helical Ag5 Cu4 (C≡CR)10 (PPh3 )5 Cl4 . Structural analysis reveals that Ag22 Cu7 exhibits multiple chirality origins, including the metal core, the metal‐ligand interface and the ligand layer. Furthermore, the circular dichroism spectra of R/S‐Ag22 Cu7 are obtained by employing appropriate chiral molecules as optical enrichment agents. DFT calculations show that Ag22 Cu7 is an eight‐electron superatom, confirm that the cluster is chirally active, and help to analyze the origins of the circular dichroism. Abstract : An alkynyl‐protected chiral bimetallic AgCu superatomic nanocluster [Ag22 Cu7 (C≡CR)16 (PPh3 )5 Cl6 ] − with a high free valence electron count is reported. This cluster exhibits multiple chirality origins, including the metal core, metal‐ligand interface and ligand layer.